Grass root leader’s perception on global warming – A case study - V. Suresh2, B. Krishnamurthy1* and (International Multidisciplinary Research Journal, 2011)
India achieved independence in 1947 after about two hundred years of British rule. Soon thereafter, in 1951, the country initiated the process of planned development to raise the living standard of its people and to open them new opportunities for a richer and more varied life. As a result of sustained efforts, considerable progress has been made in many sectors of its economy. A largely agrarian feudal economy during the time of independence has been transformed into one based on a well-developed and highly diversified infrastructure that has immense potential for industrialization. The country has made much progress in the economic sector a result of the new wave of liberalization set in motion on June 1991. Further, the government has made significant changes in environmental policy in the past two decades. Consequently, the quality of life has improved. However in spite of impressive progress in certain areas, the country still faces problems.